2008
DOI: 10.1080/00365520701875987
|View full text |Cite
|
Sign up to set email alerts
|

Acute expression of hepatitis C core protein in adult mouse liver: Mitochondrial stress and apoptosis

Abstract: Mice that are conditionally transgenic for HCV core protein, which is readily detected and morphologically associated with steatosis in individual hepatocytes, were developed. Acute expression of core protein causes mitochondrial stress, as demonstrated by a reduction in trx2 and in the apoptosis of core-positive hepatocytes. We speculate that these events could be involved in the clearance of virus during acute hepatitis C, by both reducing the burden of virus in the liver and effectively priming the immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The apoptotic property of the genotype 1a core protein has yet to be studied using the JFH-1-based infectious clone system, although previous studies have attributed both prosurvival and proapoptotic properties to it (25,30,46,57). Similar observations also have been described in overexpression studies using the genotype 1b core protein and appear to be dependent on the death stimuli and types of cells used (3,9,10,36,49,53,56,60,76). Several studies have identified domains or regions within the core protein that interfere with specific apoptosis pathways.…”
supporting
confidence: 65%
“…The apoptotic property of the genotype 1a core protein has yet to be studied using the JFH-1-based infectious clone system, although previous studies have attributed both prosurvival and proapoptotic properties to it (25,30,46,57). Similar observations also have been described in overexpression studies using the genotype 1b core protein and appear to be dependent on the death stimuli and types of cells used (3,9,10,36,49,53,56,60,76). Several studies have identified domains or regions within the core protein that interfere with specific apoptosis pathways.…”
supporting
confidence: 65%
“…During chronic inflammation, this balance is altered. Studies have shown that mitochondrial ROS production increases with viral infection [96], and NO and its derivatives (RNS) are produced in copious quantities in inflamed tissue [97]. In addition, the mechanisms for removing ROS and RNS are downregulated.…”
Section: Inflammation and Rosmentioning
confidence: 99%
“…In addition, in HCV transgenic mice, HCV core protein localizes to the mitochondria and promotes ROS generation91,92.…”
Section: Triggering Apoptosismentioning
confidence: 99%